ASP - Modelo orientado ao negócio para identificação de pontos críticos em redes ópticas - Sousa, Aminadabe Barbosa de (2018)
Best service management practices have been widely adopted by providers who maintain and manage computer network infrastructures. One of the prerequisites for adopting these practices is to maintain an effective alignment between information technology management and business management. Among the challenges service managers face while working with optical networks, identifying network high-impact redundancy points in relation to business is a difficult task. Often these managers rely on their own experience to identify points that can receive investments in redundancy in those networks and need to be prioritized in relation to planned budget. There is a growing demand for new models and tools that can support decisionmaking process. This thesis proposed a new model, capable of finding suitable points for the application of asset redundancy through simulations, which aims to mitigate optical network operation interruption risks, with a business focus. The model was implemented through a software tool named Strategic Asset Locator Program (ASP), which performs optical network scenarios simulations, with fault analysis based on topology, dependence between network elements and failure impact on business, estimating the risk related to these elements. The model output (network elements and their risks) allows service and network managers to make better decisions when analyzing risks and defining which critical points can be redundant. A case study was carried out in a real company, through simulations involving five reference network scenarios, where results were evaluated by managers and considered promising, thus contributing to Business-driven IT Management (BDIM) research area.